Factors for Satisfaction Among Providers of Ancillary Health Services in a Community-Based Cancer Prevention Program: A Pilot Study in Nevada - Emmanuel C. Gorospe; Christopher R. Cochran; Elena E. Cabb (The Scientific World Journal)
Providers of ancillary health services are essential members of any health care delivery system. They supply laboratory, radiology, and other diagnostic modalities necessary for quality medical care. Assessment of the providers' factors for satisfaction in participating in cancer prevention programs can contribute to better services and can serve as a model for other community-based health programs.We conducted a pilot survey of providers of ancillary services in the Nevada Women's Health Connection, a community breast and cervical cancer prevention program. Of the 93 participating providers, a total of 44 providers completed the survey. We subjected the survey data to factor analysis using iterative principal axis factoring with Varimax rotation. Three components of satisfaction were identified, comprising satisfaction with the (1) reimbursement process, (2) positive perception of the program, and (3) familiarity with program's requirements. All three components accounted for 72.08% of the total variance before the rotation. Amount of financial gain was not a significant factor for satisfaction among participating providers. Providers of ancillary health services were satisfied in their participation in this community-based cancer prevention program. There were three components of satisfaction identified. Further attention should be given on these issues as they have implications for quality improvement in health services for community-based programs dealing with low income and uninsured patients.